Mobile phone text message reminders to improve vaccination uptake: a systematic review - Louw, Gail (Department of Public Health and Family Medicine, 2025)
Background: Vaccination uptake remains of public health concern, despite reported improvements in vaccine access. Innovative strategies, such as mobile phone text message reminders (MPTMRs), have been explored and implemented globally to facilitate the increase in vaccination uptake and recall rates. This systematic review, employing best practice, evaluated the most recent scientific evidence for the use of MPTMRs as an intervention to improve vaccination uptake. Objective: To evaluate the effectiveness of MPTMRs on vaccination uptake in children, adolescents and adults. Methods: This systematic review included randomized controlled trials (RCT's) of caregivers of children, adolescents or adults who received MPTMRs as an intervention for improving vaccine uptake and recall visits. Studies were excluded if they did not include a comparator group or, if the comparator group was not usual care. Two authors independently searched Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Scopus, GoogleScholar and ClinicalTrials.gov to identify relevant studies published by 24 January 2024 using a pre-defined search strategy. Included studies were assessed with the Cochrane Collaboration's tool for assessing risk of bias in randomised trials. Given the heterogeneity across studies, pooled risk ratios were estimated using the random-effects model. Subgroup analyses were conducted to assess the effect of intervention type, country's economic status, study setting, and vaccination types on results of the meta-analysis. Results: We identified 25 studies (n = 64 536) for inclusion for quantitative synthesis of evidence regarding vaccination uptake. While studies were considered as having a low risk for random sequence generation, most showed an unclear risk of bias for allocation concealment. Blinding, incomplete outcome data, selective reporting and detection bias were assessed as having a low risk of bias for most studies with high attrition bias observed in seven studies. Pooled data favoured MPTMRs (RR=1.09 [95%CI: 1.06, 1.13], I2 = 76%) for improving vaccination uptake compared to usual care. Exclusion of studies of poor quality assessment improved heterogeneity and maintained the effect (RR=1.05 [95%CI: 1.03, 1.07]; I2 = 33%).